Healthcare experiences and quality of life of adults with coeliac disease: a cross‐sectional study. Issue 6 (7th May 2020) - Crocker, H.; Jenkinson, C.; Peters, M.
Abstract: Background: Coeliac disease affects many aspects of quality of life and treatment can be burdensome. Access to healthcare services is necessary for the diagnosis and management of coeliac disease. The present study aimed to investigate the healthcare experiences of adults with coeliac disease and explore the relationship between experiences and quality of life. Methods: A cross‐sectional postal survey was sent to 800 members of Coeliac UK and contained questions about diagnosis, dietary advice, follow‐up appointments, prescriptions, knowledge and information provision, and quality of life [Coeliac Disease Assessment Questionnaire (CDAQ)]. Descriptive statistics were calculated. A total problem score summarised the number of problems experienced with healthcare services. Multiple linear regression analyses were conducted to investigate experiential and demographic factors associated with quality of life. Results: An average of 5.5 problems with healthcare services was reported, with females reporting significantly more problems than males (6.5 versus 5.0, P  = 0.003). The total problem score was significantly related to the CDAQ overall index score and all CDAQ dimension scores (stigma, dietary burden, symptoms, social isolation, and worries and concerns) ( P  < 0.001). The analyses highlighted four key areas of healthcare experiences that were significantly related to quality of life: information provision, general practioners' knowledge, communication with health professionals and access to prescriptions. Conclusions: Poorer experiences of healthcare services in coeliac disease are related to worse quality of life. Improving services in the four key areas identified may help adults with coeliac disease to achieve a better quality of life. Abstract : Poorer experiences of healthcare services are correlated with poorer quality of life. This study identified four key areas for service improvement: information provision, general practioners' knowledge, communication with health professionals and access to prescriptions.